Antimicrobial and biofilm inhibiting potential of an amide derivative [N-(2′, 4′-dinitrophenyl)-3β-hydroxyurs-12-en-28-carbonamide] of ursolic acid by modulating membrane potential and quorum sensing against colistin resistant Acinetobacter baumannii. (August 2021) - Usmani, Yamina; Ahmed, Ayaz; Faizi, Shaheen; Versiani, Muhammad Ali; Shamshad, Shumaila; Khan, Saeed; Simjee, Shabana U.
Abstract: Acinetobacter baumannii is Gram-negative, an opportunistic pathogen responsible for life-threatening ventilator-associated pneumonia. World Health Organization (WHO) enlisted it as a priority pathogen for which therapeutic options need speculations. Biofilm further benefits this pathogen and aids 100–1000 folds more resistant against antimicrobials and the host immune system. In this study, ursolic acid (1 ) and its amide derivatives (2–4 ) explored for their antimicrobial and antibiofilm potential against colistin-resistant A. baumannii (CRAB) reference and clinical strains. Viability, crystal violet, microscopic, and gene expression assays further detailed the active compounds' antimicrobial and biofilm inhibition potential. Compound 4 [N-(2′, 4′-dinitrophenyl)-3 β -hydroxyurs-12-en-28-carbonamide)], a synthetic amide derivate of ursolic acid significantly inhibits bacterial growth with MIC in the range of 78–156 μg/mL against CRAB isolates. This compound failed to completely kill the CRAB isolates even at 500 μg/mL concentration, suggesting the compound's anti-virulence and bacteriostatic nature. Short and prolonged exposure of 4 inhibited or delayed the bacterial growth at sub MIC, MIC, and 2× MIC, as evident in time-kill and post-antibacterial assay. It significantly inhibited and eradicated >70% of biofilm formation at MIC and sub MIC levels compared to colistin required in high concentrations. Microscopic analysis showed disintegrated biofilm after treatment with the 4 further strengthened its antibiofilm potential. Atomic force microscopy (AFM) hinted the membrane disrupting effect of 4 at MIC's. Further it was confirmed by DiBAC4 using fluorescence-activating cells sorting (FACS), suggesting a depolarized membrane at MIC. Gene expression analysis also supported our data as it showed reduced expression of biofilm-forming ( bap ) and quorum sensing ( abaR ) genes after treatment with sub MIC of 4 . The results suggest that 4 significantly inhibit bacterial growth and biofilm mode of colistin-resistant A. baumannii . Thus, further studies are required to decipher the complete mechanism of action to develop 4 as a new pharmacophore against A. baumannii . Highlights: [N-(2′, 4′-dinitrophenyl)-3 β -hydroxyurs-12-en-28-carbonamide] inhibit growth of colistin resistant Acinetobacter baumannii. It significantly inhibits and eradicate the biofilm of Acinetobacter baumannii. It significantly reduced the gene expression of biofilm forming ( bap ) and quorum sensing ( abaR ) genes. It significantly depolarizes the membrane potential at minimum inhibitory concentration.